If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 4) + -10 = 3x + 2 Reorder the terms: 3(4 + x) + -10 = 3x + 2 (4 * 3 + x * 3) + -10 = 3x + 2 (12 + 3x) + -10 = 3x + 2 Reorder the terms: 12 + -10 + 3x = 3x + 2 Combine like terms: 12 + -10 = 2 2 + 3x = 3x + 2 Reorder the terms: 2 + 3x = 2 + 3x Add '-2' to each side of the equation. 2 + -2 + 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 0 + 3x = 2 + -2 + 3x 3x = 2 + -2 + 3x Combine like terms: 2 + -2 = 0 3x = 0 + 3x 3x = 3x Add '-3x' to each side of the equation. 3x + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 3x + -3x Combine like terms: 3x + -3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 0.45=4.5 | | -9+99= | | -26=4x-6 | | 7+26m=35+19m | | Ty-2n=y | | 7=4+9y | | -5=1/2x-5 | | (8a-23)+(9-2a)=9 | | -2(m+12)= | | 10y-6=12 | | 13=-5y-(-8) | | x+y^2=1 | | 10-17= | | (4x+17)+(x-2)=180 | | 16x-45=1x+105 | | 175=7(4+3x) | | 7m+26=35m+19 | | x-39=x+1 | | 3x-47=-2x+88 | | 42=18s+4(s+5) | | (x+4)2-38=4x | | 42-33N=44 | | 10x+5(x+12)=0 | | 16x-45+1x+105=180 | | 19=-3-2R | | (t+10)(-4)= | | 6(2g+1)=12g+1 | | X-38=-15 | | 7x-3(9-x)=15 | | a+5=-5a+53 | | 3(a+7)-4= | | 100=13x+52 |